Multiple giant intra abdominal lipomas: A rare presentation - Kshirsagar, Ashok Y. (Elsevier, 2014)
INTRODUCTION: Solitary or multiple lipomas, composed of mature fat, represents by far the most common benign mesenchymal neoplasm occurring throughout the whole body, but they rarely originate in the intestinal mesentery. PRESENTATION OF CASE: A 60-year-old male presented with left sided abdominal distension and pain since 4 months, ultrasonography and computerized tomography abdomen was suggestive of multiple well-defined fat density lesions in the lower abdomen and pelvis. USG guided fine needle aspiration cytology was conclusive of a spindle cell lesion. Exploratory laparotomy was performed and multiple major fat tissue swellings were excised. Histopathology confirmed it to be spindle cell type of lipoma. DISCUSSION: Because of the silent nature the exact prevalence of lipomas is unknown. It can arise in any location in which fat is normally present, reported intra abdominal lipomas have been very rare. Clinical manifestations depend on the size and location of the growth. In most patients, symptoms are few or absent. USG and CT scan abdomen are used for the diagnosis. Complete surgical excision being the only treatment. CONCLUSION: Intra abdominal lipoma is a very rare entity, and many cases might be ignored due to their silent nature. They might or might not present with any symptoms. Complete surgical excision being the only treatment, with a very good prognosis.